1994
DOI: 10.1121/1.408361
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and evaluation of the scattering from quadratic residue diffusers

Abstract: The scattering from quadratic residue diffusers has been predicted using methods based on the Helmholtz–Kirchhoff integral equation. The methods consisted of two boundary integral methods, and two more approximate solutions utilizing Kirchhoff’s boundary conditions. The predictions were compared to measurements made in both the near and far fields. An accurate boundary integral method which works below and above the well cutoff frequency has been found. The limitations of the more approximate methods have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Although the boundary element method used for the simulation has been found in previous studies to have very good accuracy when applied to rigid and absorptive, and reactive profiled barriers [1,2,4] and to QRD at normal incidence [10], its accuracy when dealing with QRD on a barrier has yet to be confirmed with measurements. Furthermore the numerical models assume that the admittance distribution on the QRD top surface is given by the simple plane wave admittance of the well sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the boundary element method used for the simulation has been found in previous studies to have very good accuracy when applied to rigid and absorptive, and reactive profiled barriers [1,2,4] and to QRD at normal incidence [10], its accuracy when dealing with QRD on a barrier has yet to be confirmed with measurements. Furthermore the numerical models assume that the admittance distribution on the QRD top surface is given by the simple plane wave admittance of the well sequence.…”
Section: Discussionmentioning
confidence: 99%
“…To get the true performance and array of the diffusers should be tested, but this was not possible in the 2D world. Consequently, once it has been shown that the active system is scattering as intended in the near field, the intention at this stage is to calculate the far field scattering using a Boundary Element Model as this has been shown to provide accurate predictions of diffuser scattering 20 .…”
Section: Test Environmentmentioning
confidence: 99%
“…When evaluating diffusers it is preferable to examine multiple periods, because repetition greatly influences the scattering behaviour. Previous work has shown that BEMs can produce accurate predictions of scattering from passive surfaces with wells [12] and also from surfaces with complex impedance distributions [2]. Consequently, it is possible to investigate the performance of the active diffuser in more application-realistic situations using BEMs.…”
Section: Simulation Studymentioning
confidence: 99%